Effect of agitation on mycoprotein production and its influence on mass transfer coefficient and a study on the potential of mycoprotein as antitumor agent - P.PRAKASH; SWETHA SUNKAR; K.RENUGADEVI; A.V.KARTHICK; K.RENUGADEVI; N.M.D.SAI KRISHNA; N.M.D.SAI KRISHNA (International Journal of Pharma and Bio Sciences, 2017)
Fusarium venenatum has been used as a source of mycoprotein for animal and human consumption in European countries as it is rich in protein, carbohydrates, essential amino acids and less fat content. In this study, Fusarium venenatum (CBS 458.93) was utilized for the production of mycoprotein in shake flask, 2 L, 20 L and 75 L fermenters. The effect of agitation and its influence on mass transfer coefficient were studied. The production of biomass was found to be 4.6 gm in 5 L shake flask, 5.4 gm in 2 L fermenter, 5.8gm in 20 L fermenter, and 6.3gm in 75 L fermenter. The fungal protein was checked for antitumour activity against MCF cell lines by MTT assay. The antitumor potential was found to be significant as the IC50 value was found to be 29.5 µg/ml. The toxicity was not very significant against normal Vero cells as the IC50 values was not found in the tested concentration thereby making it a potential candidate in cancer management.